التنبؤ بتدفقات الاستثمار الأجنبي المباشر في ظل مناخ الاستثمار السائد والمؤشرات الكلية للاقتصاد الجزائري -دراسة قياسية- - زروقي, أبوبكر الصديق; زروقي, يحيى (جامعة الوادي - University of Eloued, 2018)
تهدف هذه الدراسة الى ابراز مجموعة المؤشرات التي تؤثر على الاستثمار الأجنبي المباشر في الجزائر والتي تشكل في مجملها ما يعرف بمناخ الاستثمار، وتوضيح أهمية المؤشرات الكلية للاقتصاد الجزائري في تحسين المناخ الاستثماري الملائم لجذبه، ومحاولة التنبؤ بتدفقاته في السنوات المقبلة. وقد خلصت هذه الدراسة إلى أن تدفقات الاستثمار الأجنبي المباشر في الجزائر تتأثر بشكل كبير بالناتج المحلي الإجمالي وسعر الصرف، وأن حصة الجزائر من هذه التدفقات مازالت ضعيفة ولم ترقى الى المستوى المطلوب بالرغم أن القيم المتنبئ بها في السنوات المقبلة في تزايد مستمر. This study aims to highlight the set of indicators that affect foreign direct investment in Algeria, which in its entirety constitute what is known as the investment climate, and clarify the importance of the macro indicators of the Algerian economy in improving the investment climate suitable for attracting it and trying to forecast its flows in the coming years. The study found that foreign direct investment flows in Algeria are heavily affects by GDP and exchange rate and that Algeria's share of these flows remains weak and did not meet the required level, although the predicted values in the coming years are increasing.
Forecast of FDI flows following the prevailing investment climate and macroeconomic indicators of the Algerian economy
مقال
Keywords: الاستثمار الأجنبي المباشر، المناخ الاستثماري، المؤشرات الاقتصادية الكلية، النمذجة القياسية، الجزائر.